P03.05 Chlamydia re-testing at sexual health clinics has increased but further initiatives are needed for young people. (13th September 2015) - Smith, L Watchirs; Callander, D; Ali, H; Bourne, C; O'Connor, C; Lewis, D; Forrester, B; Hounsfield, V; Kaldor, J; Hellard, M; Donovan, B; Guy, R
Abstract : Introduction: Chlamydia is the most commonly notified infection in Australia; most diagnoses are in young people, and re-infections are common. Re-infection leads to onward transmission and increases the risk of reproductive morbidity and HIV transmission. Guidelines recommend re-testing 3 months following treatment to detect re-infections. We assessed trends in re-testing after a chlamydia diagnosis in Sexual Health Clinics (SHCs) in New South Wales (NSW) over a 5-year period and factors associated with re-testing. Methods: Routine patient data from 2009 to 2013 were extracted from 33 SHCs. A Chi-2 test was used to assess time trends in the proportion re-tested in 2–4 months following a chlamydia diagnosis and also 2–12 months, in a range of risk groups. Multivariate logistic regression was used to determine demographic, risk behaviour and clinic factors associated with re-testing at 2–4 months, adjusting for clinic clustering. Results: Overall 8, 646, chlamydia diagnoses were analysed and 1, 281 (15%) were re-tested in 2–4 months (23% of GBM, 25% of sex workers, 12% of young heterosexuals aged <30 years), with a significant increase over time (13% in 2009 to 18% in 2012, p < 0.01). In a broader time frame of 2–12 months, re-testing was higher at 26% (42% of GBM, 41% of sex workers, 20% of young heterosexuals) with a modest increase over time (25% to 30%, p < 0.01). Factors associated with re-testing in 2–4 months were: being GBM (adjusted odds ratio (aOR) = 1.65, 95% CI: 1.44 -1.90, p < 0.01), current sex work (aOR = 2.04, 95% CI: 1.65–2.52, p < 0.01), attending the clinic >5 times (aOR: 3.11, 95% CI: 2.62–3.70, p < 0.01) and people attending clinics with SMS reminders (aOR = 2.25, 95% CI: 1.16–4.37, p = 0.01). Conclusions: Re-testing at 2–4 months after a chlamydia diagnosis increased over time, but remains low. GBM and sex workers were more likely to be re-tested, perhaps because they were attending anyway. Attending clinics with SMS reminders increased the likelihood of re-testing. Additional strategies, such as home-collection, may be needed to increase re-testing in young heterosexuals. Disclosure of interest statement: The ACCESS Sexual Health Services Network is funded by the NSW Ministry of Health, Victorian Department of Health, Australian Capital Territory Department of Health, and the Northern Territory Department of Health.